KOMUNIKASI PENDAMPINGAN DAN PELATIHAN DIGITAL MARKETING PROGRAM PEMBERDAYAAN PEREMPUAN: STRAPPING WASTE MANAGEMENT OLEH CSR PT IKPP PERAWANG - Akromah, Rahillatul; Muljono, Pudji; Fuad Cholagi, Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the CSR pendampingan and digital marketing activities carried out in the Strapping Waste Management program of PT IKPP Perawang. The primary issue identified is the public's perception of the industry's limits and the limitations of digital marketing capabilities in the workplace. The purpose of this study is to illustrate the effectiveness of the digital marketing activities carried out by CSR PT IKPP Perawang and to analyze the effectiveness of the digital marketing activities based on the kerajinan from limbah strapping. The primary issue that has been identified is the public's perception of the industry's limits and the limitations of digital marketing skills among pengrajin women. The purpose of this study is to illustrate the pendampingan communication strategy implemented by CSR PT IKPP Perawang and to analyze the effectiveness of digital marketing strategies based on limbah strapping products. The methodology used in this study is deskriptif kualitatif; data is obtained through direct observation, interviews with primary and secondary sources of information, and literary analysis.